LDAP Implementation Cookbook - Johner, Heinz; Melot, Michel; Stranden, Harri; Widhiasta, Permana (IBM Redbooks, 1999)
The implementation and exploitation of centralized, corporate-wide directories are among the top priority projects in most organizations in the years 1999 and 2000. The need for a centralized directory emerges as organizations realize the overhead and cost involved in managing the many distributed micro and macro directories introduced in the past decade with decentralized client/server applications and network operating systems. Directories are key for a successful IT operation in medium and large environments. IBM understands this requirement and supports it by providing directory implementations based on industry standards at no additional cost on all its major platforms and even important non-IBM platforms. The IBM SecureWay Directory, formerly known as the IBM eNetwork LDAP Directory, implements the Lightweight Directory Access Protocol (LDAP) standard that has emerged quickly in the past years as a result of the demand for such a standard. This redbook will help you understand, install, and configure the IBM SecureWay Directory . It is targeted at system specialists who need to know the concepts and the detailed instructions for a successful LDAP implementation.